Landscape and Time: Retracing an Italian Theory of Landscape Through the Work of Rosario Assunto - Gentili, Andrea (Aisthesis, 2025)
The paper reconstructs the multifaceted concept of landscape by tracing its historical development and examining the engagement of Italian aesthetologist Rosario Assunto with this notion in the 1970s, a period when the notion of landscape had been largely overlooked by both philosophical and political movements focused on ecology and the environment. Assunto reconfigures landscape as an aesthetic category that transcends its traditional association with art, extending it into a phenomenological and historical framework. Central to his analysis is the temporality of landscape, particularly as manifested in the organic movement of the animal. This approach challenges rigid conservationist paradigms and provides a dynamic conceptual model that remains highly relevant for contemporary discussions on landscape regeneration and restoration.